2020
DOI: 10.7150/ijms.42805
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of Differentiation 1 (Id1) in Cancer and Cancer Therapy

Abstract: The inhibitor of DNA binding (Id) proteins are regulators of cell cycle and cell differentiation. Of all Id family proteins, Id1 is mostly linked to tumorigenesis, cellular senescence as well as cell proliferation and survival. Id1 is a stem cell-like gene more than a classical oncogene. Id1 is overexpressed in numerous types of cancers and exerts its promotion effect to these tumors through different pathways. Briefly, Id1 was found significantly correlated with EMT-related proteins, K-Ras signaling, EGFR sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 121 publications
(137 reference statements)
0
41
0
1
Order By: Relevance
“…ID1 protein is a member of the helix-loop-helix family of transcriptional regulatory proteins. As a known target of USP1 10 , 13 , the dysregulation of ID1 has been widely reported in multiple types of human tumors, which is essential for processes such as proliferation, cell migration and stem cell renewal 19 - 21 . In B-ALL patients, high expression level of ID1 is associated with the poor outcome 22 .…”
Section: Discussionmentioning
confidence: 99%
“…ID1 protein is a member of the helix-loop-helix family of transcriptional regulatory proteins. As a known target of USP1 10 , 13 , the dysregulation of ID1 has been widely reported in multiple types of human tumors, which is essential for processes such as proliferation, cell migration and stem cell renewal 19 - 21 . In B-ALL patients, high expression level of ID1 is associated with the poor outcome 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Drugs such as tetramethylpyrazine, vinblastine, crizotinib, and fucoidan were found to inhibit tumor growth or metastasis by targeting ID1-associated signaling pathways. 22 We found that ID1 was a key target of regorafenib, and speculate that the combination therapy of regorafenib and the above-mentioned agents may benefit to improve the therapeutic effect of HCC.…”
Section: Regorafenib Suppresses Tumor Growth and Vm Formation In Pdmentioning
confidence: 77%
“…A variety of compounds have been found to exert antitumor effects via targeting ID1 or its related signaling pathways 15,21 . ID1 represents a promising target of antitumor therapeutics, on the strength of its cancer‐promoting properties 22 . Furtherly, numerous studies have revealed that ID1 plays an important role in tumor metastasis and angiogenesis in lung cancer, colon cancer, breast cancer and other tumors 15,21,23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we have demonstrated that the over-expression of ID1 effectively promoted the carcinogenesis of OSCC [12,13]. ID1 is one of the inhibitors of DNA binding (Id) proteins [27]. During development, the Id proteins play a key role in the regulation of cell-cycle progression and cell differentiation by modulating different cellcycle regulators both by direct and indirect mechanisms [28].…”
Section: Discussionmentioning
confidence: 99%